2011
DOI: 10.1128/aem.05204-11
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Psychropiezophilic Alphaproteobacterium

Abstract: Cultivated psychropiezophilic (low-temperature-and high-pressure-adapted) bacteria are currently restricted to phylogenetically narrow groupings capable of growth under nutrient-replete conditions, limiting current knowledge of the extant functional attributes and evolutionary constraints of diverse microorganisms inhabiting the cold, deep ocean. This study documents the isolation of a deep-sea bacterium following dilution-to-extinction cultivation using a natural seawater medium at high hydrostatic pressure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 86 publications
0
26
0
1
Order By: Relevance
“…This results in reduced BGE when growth is constrained by factors such as temperature and nutrient supply, rather than organic carbon (energy) (del Giorgio and Cole, 1998). Previous studies have demonstrated that the growth of barophilic bacteria isolated from depths X3584 m is affected by temperature, pressure and substrate supply (Yayanos, 1986;Wirsen and Molyneaux, 1999;Eloe et al, 2011), with the production of new biomass declining rapidly as temperatures drop below 0 1C (Yayanos, 1986). Experiments conducted on barotolerant microbial communities from much shallower (p2003 m), Arctic sediments have demonstrated that the effects of labile substrate supply on bacterial catabolic activities predominate over those of temperature, salinity and pressure (MeyerReil and Kö ster, 1992;Arnosti et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…This results in reduced BGE when growth is constrained by factors such as temperature and nutrient supply, rather than organic carbon (energy) (del Giorgio and Cole, 1998). Previous studies have demonstrated that the growth of barophilic bacteria isolated from depths X3584 m is affected by temperature, pressure and substrate supply (Yayanos, 1986;Wirsen and Molyneaux, 1999;Eloe et al, 2011), with the production of new biomass declining rapidly as temperatures drop below 0 1C (Yayanos, 1986). Experiments conducted on barotolerant microbial communities from much shallower (p2003 m), Arctic sediments have demonstrated that the effects of labile substrate supply on bacterial catabolic activities predominate over those of temperature, salinity and pressure (MeyerReil and Kö ster, 1992;Arnosti et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Clade members are ubiquitous in temperate and polar oceans (30); the latter include sea ice habitats, in which Roseobacter is a major bacterial phylotype (31,32). Roseobacters are also abundant in coastal sediments (33), deep pelagic ocean (34), and deep-sea sediments (35).…”
Section: Introductionmentioning
confidence: 99%
“…Rhodobacterales bacterium belonging to the class of α-proteobacteria that is known living in a low temperature and high pressure (Psychropiezophiles) were f ound in site II, while Aphanothece sp. (Chroococcales class) which are able to live in high salinity (halophiles) were found in site I (Sarma & Arora, 2001;Eloe et al, 2011). There were types of Roseovarius sp.…”
Section: T-rflp Analysismentioning
confidence: 97%